Evaluation of Elements of the Nursing Worklife Model Using Unit-Level Data. (February 2016) - Ballard, Nancy; Boyle, Diane K.; Bott, Marjorie J.
The practice environment is important to nurse satisfaction and patient outcomes. Laschinger and Leiter posited causal relationships by development and testing of the Nursing Worklife Model (NWLM). Using a secondary analysis of unit-level data ( N = 3, 203; medical, surgical, medical–surgical, critical-care, and step-down units) from the 2011 National Database for Nursing Quality Indicators®, hypothesized pathways of the NWLM were tested using structural equation modeling. Practice Environment subscales developed by Lake were used to operationalize model variables with job enjoyment being the outcome variable. Positive pathways identified in the original causal model were supported. However, using an iterative process, additional pathways were identified that improved model fit (comparative fit index = 0.99; root mean square error of approximation = 0.06; standardized root mean square residual = 0.002). Nurse manager ability, leadership, and support had direct links to job enjoyment as well as other elements of the model. Development of nurse managers is important to the retention of clinical nurses in the hospital setting.